A informática educativa na Rede Municipal de Educação de SP (1994-2013) - Gabriel, Ana Paula Camilo (2015)
This research aims to examine the introduction of Educational Computing and its practices in the municipal schools of São Paulo. The study begins in 1994 with Decree 34.160/1994, which established Educational Computing Laboratories (LIEs) in the São Paulo Municipal Public School System, and continues until 2013 with the publishing of Decree 54.452/2013, which established within the Municipal Secretary of Education the program Mais Educação São Paulo , Program for Curricular and Administrative Reorganization, Amplification and Strengthening for the São Paulo Municipal School System. The analysis examines the legislation and official documentation as well as the pertinent bibliography. In order to verify which Educational Computing practices were developed, a case study was carried out at the municipal elementary school, EMEF Henrique Pegado. Using Oral History procedures, teachers involved narrated their trajectories as teacher-advisors in Educational Computing POIE, presented the concepts of Educational Computing that they adopted, described the infrastructure and logistical conditions encountered in Computer Laboratories and adaptations realized, and enumerated their practices in a variety of day-to-day activities